Design of zinc porphyrin‐perylene diimide donor‐bridge‐acceptor chromophores for large second‐order nonlinear optical response: A theoretical exploration. Issue 10 (15th November 2017) - Hu, Zhubin; Sun, Zhenrong; Sun, Haitao
Abstract: The electronic structures and second‐order nonlinear optical (NLO) properties of a series of zinc porphyrin (ZnP)‐perylene diimide (PDI) donor‐bridge‐acceptor (D‐π‐A) molecules have been investigated using density functional theory (DFT) and time‐dependent DFT (TDDFT). The results show that these compounds possess excellent second‐order NLO properties and large static first hyperpolarizabilities (β0 ) values on the order of 10 3 – 10 4 esu −30 . A DFT benchmark calculation of β0 value was first performed, confirming the optimally tuned range‐separated functionals (LC‐BLYP* and ωB97X*) can produce similar magnitudes for β0 as Møller–Plesset second‐order perturbation (MP2) calculations. The magnitudes of β0 values were studied as a function of different types of bridges: oligo‐ p ‐phenylenevinylene (OPV), carbon‐bridged oligo‐ p ‐phenylenevinylene (COPV), oligo‐thienylenevinylene (OTV), carbon‐bridged oligo‐thienylenevinylene (COTV), and also the length of π‐bridges. The calculated β0 values were found to be inversely related to the bond length alternation (BLA) values of various π‐bridges. Next, we found that the static β0 value of designed ZnP‐COTV1 ‐PDI molecule can be significantly enhanced by finely tuning the dihedral angles between the π‐bridge and ZnP donor or PDI acceptor. The calculated β0 value is also sensitive to the substitution positions of PDI, that is, ortho‐(α‐), bay‐(β‐), nitrogen‐(N‐). A two‐level model was proven to be useful for the qualitative description of the β0 values and further the substantial oscillator strength and the difference in transition dipole moments between the ground and excited state mainly contribute to the large β0 values. The presented work will be beneficial for potential applications of the ZnP‐PDI‐based chromophores in the optoelectronic devices and high‐performance NLO materials. Abstract : Zinc porphyrin (ZnP)‐perylene diimide (PDI) donor‐bridge‐acceptor (D‐π‐A) compounds possess excellent second‐order nonlinear optical properties, and large static first hyperpolarizabilities (β0 ). β0 values can be significantly increased by finely tuning the dihedral angles between the π‐bridge and ZnP donor or PDI acceptor. The calculated hyperpolarizability value is found to be also sensitive to the substitution position of PDI.